Basic freeway segments : capacity and level of service analysis - Abeyawardena, Wanniachchige Devini Sathma Barnes; Ampol Karoonsoontawong; Kunnawee Kanitpong; Surachet Pravinvongvuth (Pathum Thani : Asian Institute of Technology, 2018)
Uninterrupted flow exists in its purest form on freeways. On these facilities, all entering and exiting vehicles do so by high speed ramps designed to minimize the disruption to the through vehicle traffic stream. There is no direct access to any land parcel, and there are no fixed causes of interruption to traffic external to the traffic stream which means there are no traffic signals, stop signs or at-grade intersections which ultimately affect the free flow speed thereby affecting the capacity and the level of service of the basic freeway segment under study. Level of service measures the working conditions within a stream of traffic thereby denoting the drivers insight of those conditions. Level of service on a basic freeway segment is defined by density of the traffic flow. In this research, the process to determine the level of service is described in detail by using the methodology of the Highway Capacity Manual 2010. Fully automated MS Excel worksheets were developed to facilitate the sensitivity of the parameters that affects a basic freeway segment by testing the given examples in the Highway Capacity Manual; since the Transportation Research Board does not endorse any commercial software to do the same.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil and Infrastructure Engineering
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Highway capacity; Traffic flow; Traffic engineering